Manual de gestión para captación de capital social en la Cooperativa de Ahorro y Crédito Cámara de Comercio del Cantón Bolívar - Zambrano Loor, Darío Gabriel (2022)
The investigation was carried out with the purpose of elaborating a management manual for the capture of social capital in the Cooperative of Savings and Credit Chamber of Commerce of the canton Bolívar Ltda., for which a methodology with a mixed approach was developed, whose stages included the following: (1) characterization of the institution by reviewing the website and analysis of the evolution of capital gains using the historical method and statistical graphs; (2) diagnosis of the current process of raising social capital carried out through the application of an observation sheet in the cooperative's facilities, and two semi- structured interviews, one addressed to the manager and the other to the person responsible for raising funds; These data collection instruments were validated through the Content Validity Coefficient; (3) proposal of improvement strategies to encourage the capture of social capital based on the analysis of internal and external factors carried out through a SWOT matrix; and (4) development of a management manual for raising social capital structured according to the elements proposed by the Superintendence of Popular and Solidarity Economy, and subsequently validated by a panel of experts. The results determined that the cooperative has administrative and advertising weaknesses, as well as a lack of financial tools and services. In conclusion, the application of the proposed improvements, as well as the management manual, allows greater efficiency in the processes and an increase in the values of capturing social capital.